Further insight into the coordination of 2,5-dicarbothioamidopyrroles: the case of Cu and Co complexes - Karagiannidis, L.; Gale, P.; Light, M; Massi, Massimiliano; Ogden, Mark (The Royal Society of Chemistry, 2011)
The coordination chemistry of 2,5-dicarbothioamidopyrrole ligands, namely N2,N5-dibutyl-3,4-diphenyl-1H-pyrrole-2,5-bis(carbothioamide) and N2,N5,3,4-tetraphenyl-1H-pyrrole-2,5-10 bis(carbothioamide) has been investigated with Cu(II) metal centres by means of X-ray crystallography. This resulted in the formation of the expected planar S,N,S’ coordinated complex for the former ligand, and unexpected ring-closure reactions, with formation of benzothiazole sidearms for the latter. Both Cu(II) and Cu(I), used in large excess, were found to favour the ring-closurereaction, although the structural characterisation of the resulting complexes, contained only 15 Cu(II) cations, with varying coordination geometries ranging from square planar and square-based pyramidal to tetrahedral. By repeating the reaction using a slight excess of Cu(II) (2:1) two more different structures were obtained where the metal was coordinated to the original ligand, N2,N5,3,4-tetraphenyl-1H-pyrrole-2,5-bis(carbothioamide), or to the mixed ligand where only one of the thioamide substituents had converted to a benzothiazole. The essential role of Cu for the 20 ring closure reaction was also established by comparing its complex with structural features of the analogous Co(II) complex, the latter revealing no ring closure to give benzothiazole substituents and co-crystallisation of a mixed Co(II)/Co(III) complex.Finally, the structure and photophysical properties of the corresponding 3,4-diphenyl-2,5-bis(benzothiozol-5-yl)-pyrrole ligand, obtained via treatment of the thioamide with K3[Fe(CN)6], were also investigated revealing a blue-centered 25 emission.